(untitled) (European Journal of Interdisciplinary Research and Development, 2022)
The yield was 58.0 t/ha in the recommended control variant for the Sharkiya-2 variety and 66.1 t/ha for the “Saratoni” variety. Compared with the recommended control, in the variants with the application of 200-250 and 300 kg/ha of nitrogen fertilizers, the yield was 9.7-17.1-17.7% for the Sharkiya-2 variety, 10.4 for the Saratoni variety; It reached 15.7 and 16.6%. As the yield increased, the cost of 1 ton of products decreased from 201.6 thousand sums to 179.3 thousand sums for the Sharkiya-2 variety, from 208.7 thousand sums to 167.5 thousand sums for the Saratoni variety. The level of profitability depends on the yield and total costs, and the highest rate (background + N250) was 39.5% for the Sharkiya-2 variety and 49.2% for the Saratoni variety.